2018
DOI: 10.1159/000489952
|View full text |Cite
|
Sign up to set email alerts
|

Allograft Inflammatory Factor-1 Mediates Macrophage-Induced Impairment of Insulin Signaling in Adipocytes

Abstract: Background/Aims: Allograft inflammatory factor-1 (AIF-1) is an inflammatory cytokine produced mainly by macrophages within human white adipose tissue. Its expression is increased in obese subjects and positively correlated with insulin resistance. The purpose of this study is to characterize the regulatory role of AIF-1 in insulin signaling of adipocyte. Methods: AIF-1 was over-expressed via transfection of AIF-1 cDNA into murine RAW 264.7 macrophages, and the constitutive expression of AIF-1 was decreased via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…However, the effect of AIF-1 on NF-kB pathway and inflammation can be alleviated by the BAY 11-7082, a NF-kB signaling inhibitor. It is consistent with that BAY 11-7082 has been reported to attenuate the elevated levels of IL-6 and TNF-a (Kumar et al, 2012;Ren et al, 2018;Zabrodskii et al, 2018). Previous studies have demonstrated that AIF-1 is encoded in the region of chromosome 6p21.3, which is clustered with genes related to the inflammatory responses in human (Iris et al, 1993;Deininger et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, the effect of AIF-1 on NF-kB pathway and inflammation can be alleviated by the BAY 11-7082, a NF-kB signaling inhibitor. It is consistent with that BAY 11-7082 has been reported to attenuate the elevated levels of IL-6 and TNF-a (Kumar et al, 2012;Ren et al, 2018;Zabrodskii et al, 2018). Previous studies have demonstrated that AIF-1 is encoded in the region of chromosome 6p21.3, which is clustered with genes related to the inflammatory responses in human (Iris et al, 1993;Deininger et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the production of IL-6 and TNF-a were decreased after BAY 11-7082 treatment. It is consistent with that BAY 11-7082 has been reported to attenuate the elevated levels of IL-6 and TNF-a (Kumar et al, 2012;Ren et al, 2018;Zabrodskii et al, 2018). Specifically, data revealed that peritoneal mesothelial cells, as an important cellular model, were shown to be related with fibrotic change in mouse peritoneal mesothelial cells (Bot et al, 2003;Shin et al, 2017;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Short interference RNA for allograft inflammatory factor 1 (AIF-1) was synthesized (targeted sequence CCTAGAGCTGAAGAGATTA, siAIF-1) with negative control (target sequence: TTCTCCGAACGTGTCACGT, siRNA) as we previously described (Ren, Lin, Tang, Yue, & Zhao, 2018). The RNA was transfected into macrophage RAW264.7 with a Sofast kit (Xiamen, Fujian, China) according to the manufacturer's instructions.…”
Section: Cell Transfectionmentioning
confidence: 99%